INFLUENCE OF FABRICATION PARAMETERS ON PROPERTIES AND PERFORMANCE OF POLY(VINYLIDENE FLUORIDE) MEMBRANES FOR MEMBRANE DISTILLATION - MAT NAWI, NORMI IZATI (2018)
Water scarcity has become a serious global issue. To cope with this situation, membrane distillation (MD) come to the fore as an alternative solution.